Implant stability and marginal bone level of microgrooved zirconia dental implants: A 3-month experimental study on dogs - Delgado-Ruiz, Rafael Arcesio; Marković, Aleksa; Calvo-Guirado, Jose Luis; Lazić, Zoran; Piattelli, Adriano; Boticelli, Daniele; Mate-Sanchez, Jose Eduardo; Negri, Bruno; Ramirez-Fernandez, Maria Piedad; Mišić, Tijana (Vojnosanitetski pregled, 2014)
Background/Aim.The modification of implant surfaces could affect mechanical implant stability as well as dynamics and quality of peri-implant bone healing. The aim of this 3-month experimental study in dogs was to investigate implant stability, marginal bone levels and bone tissue response to zirconia dental implants with two laser-micro-grooved intraosseous surfaces in comparison with nongrooved sandblasted zirconia and sandblasted, high-temperature etched titanium implants. Methods. Implant surface characterization was performed using optical interferometric profilometry and energy dispersive X-ray spectroscopy. A total of 96 implants (4 mm in diameter and 10 mm in length) were inserted randomly in both sides of the lower jaw of 12 Fox Hound dogs divided into groups of 24 each: the control (titanium), the group A (sandblasted zirconia), the group B (sandblasted zirconia plus microgrooved neck) and the group C (sandblasted zirconia plus all microgrooved). All the implants were immediately loaded. Insertion torque, periotest values, radiographic crestal bone level and removal torque were recorded during the 3-month follow-up. Qualitative scanning electon microscope (SEM) analysis of the bone-implant interfaces of each group was performed. Results. Insertion torque values were higher in the group C and control implants (p < 0.05). Periotest values increased in all the periods in proportion to the extent of microgrooving as follows: the group C > the control > the group B > the group A (p < 0.05). Radiographic measurements showed minimal crestal bone loss at 3 months for microgrooved zirconia implants (groups C and B) and control implants compared with the group A implants (p < 0.05).  The removal torque values increased with time for all the groups as follows: the group C > the control > the group B > the group A (p < 0.05). SEM showed that implant surfaces of the groups B and C had an extra bone growth inside the microgrooves that corresponded to the shape and direction of the microgrooves. Conclusion. The addition of microgrooves to the entire intraosseous surface of zirconia dental implants enhances primary and secondary implant stability, promotes bone tissue ingrowth and preserves crestal bone levels.
Keywords: dental implants; surface properties; biomechanics; microscopy; electron; scanning; alveolar bone loss; zirconium; titanium; dogs